Resposta :
Resposta:
f(3)=-1
Explicação passo-a-passo:
se f(x)=x²-4x+2,
logo,
f(3)=3²-4.3+2
f(3)=9-12+2
f(3)=-3+2
f(3)=-1
Resposta:
OLÁ
- ❊ para calcular a função basta substituir x por 3
RESOLUÇÃO
[tex] \boxed{ \begin{array}{c} \\ \large{ \sf{f(x) = {x}^{2} - 4x + 2}} \\ \\ \large{ \sf{f(3) = {3}^{2} - 4 \times 3 + 2 }} \\ \\ \large{ \sf{f(3) = 9 - 4 \times 3 + 2}} \\ \\ \large{ \sf{f(3) = 9 - 12 + 2}}\\ \\ \large{ \sf{f(3) = - 3 + 2}} \\ \\ \large{ \sf{ \blue{f(3) = - 1}}}\end{array}}[/tex]
_______
espero ter ajudado
__________________
![Ver imagem ANDREYLUCAS15399](https://pt-static.z-dn.net/files/dd7/c62dcb23d2df17b6b38956bdebab5ebb.jpg)